Reconfiguration of dynamic brain networks in heart failure with preserved ejection fraction: Linking neurovascular coupling and cardiac dysfunction - Xiulin Liang; Qinghua Zhang; Chuanlong Zhang; Jingjing Liu; Pengcheng Sang; Qing Mao; Lei Wang (Brain Research Bulletin)
Purpose: This study aimed to investigate the alterations in static and dynamic network topology properties in patients with heart failure with preserved ejection fraction (HFpEF). Methods: Functional magnetic resonance imaging (fMRI) was obtained from 41 patients with HFpEF and 39 healthy individuals. The topology properties of static and dynamic functional brain networks were examined using graph theory methodologies, and the correlation between abnormal brain network characteristics and clinical features was assessed. Results: (1) Static network topology properties exhibited significantly decreased local network efficiency among patients with HFpEF. The connectivity strength and information processing efficiency were diminished in the left parahippocampal gyrus, left cingulate gyrus, and right insular gyrus brain regions, and improved in the left thalamus, right fusiform gyrus, and right precuneus regions. (2) Dynamic network topology properties of patients with HFpEF showed decreased variability in critical nodes and brain subregions (e.g., the superior frontal gyrus, left amygdala, and left fusiform gyrus) and compensatory increases in the variability of specific regions (e.g., right insular gyrus, right postcentral gyrus, and right temporal gyrus). (3) In HFpEF, the static and dynamic functional brain network topology properties of the fusiform gyrus, cingulate gyrus, superior temporal gyrus, precuneus, parahippocampal gyrus, insular gyrus, and amygdala regions were significantly correlated with cardiac structural and functional indices, such as LVDd, LVMI, and E/e′ ratio. Conclusion: Alterations in cardiac structure and function in HFpEF may affect the dynamic activity of specific brain networks through neurovascular coupling mechanisms.